Antibiotic Resistance of Diverse Bacteria from Aquaculture in Borneo - Kathleen, Michelle Mikal; Samuel, Lihan; Felecia, C.; Reagan Entigu, ak Linton @ Jerah; Kasing, Apun; Lesley Maurice, Bilung; Toh, S.C. (Hindawi Publishing Corporation, 2016)
The administration of antimicrobials in aquaculture provides a selective pressure creating a reservoir of multiple resistant bacteria in the cultured fish and shrimps as well as the aquaculture environment. The objective of this study was to determine the extent of antibiotic resistance in aquaculture products and aquaculture’s surrounding environment in Sarawak, Malaysian Borneo. Ninetyfour identified bacterial isolates constituted of 17 genera were isolated from sediment, water, and cultured organisms (fish and shrimp) in selected aquaculture farms. These isolates were tested for their antibiotic resistance against 22 antibiotics from several groups using the disk diffusion method. The results show that the highest resistance was observed towards streptomycin (85%).